Hybrid Algorithm Based on Bidirectional A* and Floodfill Applied to Coverage Path Planning for AGVs - Carvalho, Lucas L. M.; Marques, Diogo G.; Castro, Gabriel G.R.; Tuxi, Thiago M.; Pinto, Milena F. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
This paper presents a hybrid Coverage Path Plan-ning (CPP) strategy that integrates the Floodfill algorithm with bidirectional A * (BA *) to optimize navigation for Autonomous Ground Vehicles (AGVs) tasked with inspecting photovoltaic farms. The proposed approach leverages the global exploration capabilities of Floodfill with the heuristic efficiency of bidirectional A *, enabling fast and complete area coverage while min-imizing redundant traversal and computational overhead. The framework is validated in a Software-In-the-Loop (SITL) simulation using Gazebo and ROS, and its performance is benchmarked against conventional Floodfill, Floodfill with A *, and Wavefront-based methods. Results demonstrate significant improvements in coverage efficiency, path smoothness, and execution time, highlighting the method's potential for real-world large-scale CPP applications. The proposed method achieved overlap and direction change rates below 1 %, significantly improving path efficiency.